Peptidoglycan from Immunobiotic Lactobacillus rhamnosus Improves Resistance of Infant Mice to Respiratory Syncytial Viral Infection and Secondary Pneumococcal Pneumonia - Clua, Patricia; Kanmani, Paulraj; Zelaya, Hortensia; Tada, Asuka; Kober, A. K. M. Humayun; Salva, Susana; Alvarez, Susana; Kitazawa, Haruki; Villena, Julio (Frontiers in Immunology, 2017)
Several research works have demonstrated that beneficial microbes with the capacity to modulate the mucosal immune system (immunobiotics) are an interesting alternative to improve the outcome of bacterial and viral respiratory infections. Among the immunobiotic strains with the capacity to beneficially modulate respiratory immunity, Lactobacillus rhamnosus CRL1505 has outstanding properties. Although we have significantly advanced in demonstrating the capacity of L. rhamnosus CRL1505 to improve resistance against respiratory infections as well as in the cellular and molecular mechanisms involved in its beneficial activities, the potential protective ability of this strain or its immunomodulatory cellular fractions in the context of a secondary bacterial pneumonia has not been addressed before. In this work, we demonstrated that the nasal priming with non-viable L. rhamnosus CRL1505 or its purified peptidoglycan differentially modulated the respiratory innate antiviral immune response triggered by toll-like receptor 3 activation in infant mice, improving the resistance to primary respiratory syncytial virus (RSV) infection, and secondary pneumococcal pneumonia. In association with the protection against RSV-pneumococcal superinfection, we found that peptidoglycan from L. rhamnosus CRL1505 significantly improved lung CD3+CD4+IFN-γ+, and CD3+CD4+IL-10+ T cells as well as CD11c+SiglecF+IFN-β+ alveolar macrophages with the consequent increases of IFN-γ, IL-10, and IFN-β in the respiratory tract. Our results also showed that the increase of these three cytokines is necessary to achieve protection against respiratory superinfection since each of them are involved in different aspect of the secondary pneumococcal pneumonia that have to be controlled in order to reduce the severity of the infectious disease: lung pneumococcal colonization, bacteremia, and inflammatory-mediated lung tissue injury.